AKULTURASI BUDAYA BUGIS DAN MAKASSAR DALAM NOVEL LAKUNA KARYA KHRISNA PABICHARA (KAJIAN SEMIOTIK CHARLES SANDERS PEIRCE QUALISIGN): Array - Yudmianti, Siti Vitandari; Mulasih, Mulasih (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2022)
The background of this research is cultural acculturation that can occur in various forms and causes. It can be in the form of language, cultural activities, and others. Showing cultural acculturation is one of the activities of maintaining culture. Through the novel, a writer can include elements of cultural acculturation of an area so that it can be learned from it cultural acculturation that occurs between two cultures. The novel entitled Lakuna by Khrisna Pabichara (2021) is one of the novels that contains the acculturation of Bugis and Makassar cultures. This study aims to describe the acculturation of Bugis and Makassar cultures in this novel. The approach used in this study is Charles Sanders Peirce's semiotic approach in the form of qualisigns. The method used in this study is descriptive analysis. The data collection technique used is the read and record technique. The results showed that there were signs of acculturation of Bugis and Makassar qualisign cultures, namely 6 quotations that showed differences in the quality of a person based on noble blood and non-nobles which were included in one of the cultural customs of the Bugis Tribe, namely the distinguishing custom or custom of propriety.